Current topics in developmental biology - Schatten, Gerald; ScienceDirect eBooks (San Diego ; London : Academic Press, 2006)
Current Topics in Developmental Biology provides a comprehensive survey of the major topics in the field of developmental biology. The volumes are valuable to researchers in animal and plant development, as well as to students and professionals who want an introduction to cellular and molecular mechanisms of development. The series has recently passed its 30-year mark, making it the longest-running forum for contemporary issues in developmental biology. * Includes over 25 color tables * Topics covered include stem cells, zygotes, hepatocyte cell cycle, and mammary gland functions in seals * Six chapters edited by the most authoritative figures in their fields of study.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Embryology; Cytogenetics; Cytogenetics; Embryology; Electronic books